2006
DOI: 10.1523/jneurosci.4664-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Axonal and Somatic Na Channels to Action Potential Initiation in Cerebellar Purkinje Neurons

Abstract: Neuronal excitability is likely to be regulated by the site of action potential initiation, the location on a neuron that crosses threshold first. Although initiation is axonal in many neurons, in Purkinje cells, somatic conductances can generate spontaneous action potentials, suggesting that the perisomatic region (soma and/or initial segment) contributes to spike initiation and may regulate firing. To identify directly the cellular regions at which Na channel modulation significantly influences firing, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 48 publications
9
116
1
Order By: Relevance
“…One criterion for the location of action potential initiation is sensitivity of action potential threshold to pharmacologically reduced sodium channel density (Colbert and Johnston 1996;Khaliq and Raman 2006;Meeks and Mennerick 2007;Palmer and Stuart 2006). We found that local tetrodotoxin application to the proximal axon of granule neurons (15-30 m) produced a shift in spike threshold, assessed by phase plot analysis (Fig.…”
Section: E F and H)mentioning
confidence: 85%
“…One criterion for the location of action potential initiation is sensitivity of action potential threshold to pharmacologically reduced sodium channel density (Colbert and Johnston 1996;Khaliq and Raman 2006;Meeks and Mennerick 2007;Palmer and Stuart 2006). We found that local tetrodotoxin application to the proximal axon of granule neurons (15-30 m) produced a shift in spike threshold, assessed by phase plot analysis (Fig.…”
Section: E F and H)mentioning
confidence: 85%
“…Although eAPs recorded from local field potentials (LFPs) are thought to reflect the derivative of intracellularly recorded APs (iAPs), the origin of eAPs monitored by cell-attached recording is controversial (Raastad and Shepherd, 2003;Khaliq and Raman, 2006;Perkins, 2006). Therefore, we simultaneously recorded and compared the waveforms of iAPs (whole cell) and eAPs (cell attached) from cell bodies of CA3 pyramidal cells and eAPs recorded in LFPs (Fig.…”
Section: Extracellular Aps Monitored By Cell-attached Recordingmentioning
confidence: 99%
“…The generation, modulation, and duration of axonal action potentials depend on both the high densities and the specific types of ion channels found at the AIS (Hedstrom and Rasband, 2006;Khaliq and Raman, 2006;Shu et al, 2007). Kv1 channels are prominent in axons and nerve terminals (Gu et al, 2003;Trimmer and Rhodes, 2004) and modulate action potentials (Kole et al, 2007).…”
Section: Multiple Kv1 Channel Subunits Are Located At the Axon Initiamentioning
confidence: 99%